The Sistani cycle of epics and Iran's national history : on the margins of historiography - Gazerani, Saghi. (Studies in Persian Cultural History, 2015)
This work examines the entire corpus of the Sistani Cycle of Epics , both parts included in Ferdowsi's Shāhnāmeh and those appearing in separate manuscripts. It argues that the so-called "epic literature" of Iran constitutes a kind of historiography, encapsulating reflections of watershed events of Iran's antiquity. By examining the symbiotic relationship of the texts' content and form, the underpinning discourse of the various stories is revealed to have been shaped by polemics of political legitimacy and religious conflict. This discourse, however, is not abstract. The stories narrate, within their generic constraint, some of the affairs of the Sistani kingdom and its relationship to the Parthian throne, mainly from the first century BCE to the end of the second century CE.